Estrogen Modulates the Sensitivity of Lung Vagal C Fibers in Female Rats Exposed to Intermittent Hypoxia - Huang, Ya-Chen; Yuan, Zung Fan; Yang, Chang-Huan; Shen, Yan-Jhih; Lin, Jyun-Yi; Lai, Ching Jung (Frontiers in Physiology, 2018)
The main characteristic of obstructive sleep apnea is exposure to intermittent hypoxia (IH), and is associated with hyperreactive airway diseases and lung inflammation. Sensitization of lung vagal C fibers (LVCFs) by inflammatory mediators may play a central role in the pathogenesis of airway hypersensitivity. Estrogen interferes with inflammatory signaling pathways, which may modulate the process of hyperreactive airways in females. In this study, we investigated the effects of IH on the reflex and afferent responses of LVCFs and lung inflammation in adult female rats, and the role of estrogen in these responses. Intact and ovariectomized (OVX) female rats were exposed to room air (RA) or IH for 14 consecutive days. On day 15, IH enhanced apneic responses to right atrial injection of chemical stimulants of LVCFs (e.g. capsaicin, phenylbiguanide, and a,b-methylene-ATP) in intact anesthetized females. OVX combined IH exposure markedly produced an augmented apneic response to the same dose of stimulants in rats compared with all other groups. The apneic responses to the stimulants were completely abrogated by bilateral vagotomy or perivagal capsaicin treatment, which blocked the neural conduction of LVCFs. Our electrophysiological experiments consistently revealed that OVX greatly potentiated the excitability of LVCFs to these stimulants in IH-exposed rats. Moreover, LVCF hypersensitivity in OVX rats prior to IH exposure was accompanied by enhanced lung inflammation as shown by elevated inflammatory cell infiltration in bronchoalveolar lavage fluid and increased lung lipid peroxidation and protein expression of inflammatory cytokines. 17β-estradiol (E2) replacement at a low concentration (30 μg/ml), but not at high concentrations (50 and 150 μg/ml), prevented the augmenting effects of OVX on LVCF sensitivity and lung inflammation caused by IH. These results suggest that ovarian hormones prevent the enhancement of LVCF sensitivity and lung inflammation by IH in female rats, which are related to the effect of low-dose estrogen.